0
$\begingroup$

Given the translation operators (and/or boost) on position and momentum as ($\hbar$=1) $$U_x=e^{iap}\rightarrow U^\dagger_xxU_x=x+a$$ $$U_p=e^{-abx}\rightarrow U^\dagger_ppU_p=p+b$$ And am asked to calculate $$\langle x|U_p^\dagger U_x^\dagger |\psi\rangle$$

My approach (notation is a little messy in terms of missing daggers when acting left or right, etc):

$$U_p|x\rangle=|x\rangle=\langle x|U_p^\dagger$$ $$U_x|x\rangle = \langle x|U_x^\dagger=|x+a\rangle$$ So we operate $U_p$ left then $U_x$ left to get $$\langle x|U_p^\dagger U_x^\dagger |\psi\rangle=\langle x+a|\psi\rangle = \psi(x+a)$$ I feel like I am missing something about $U_p|x\rangle$ , but I can't think of what

$\endgroup$
  • $\begingroup$ You are equating bras to kets which is completely wrong. $\endgroup$ – jinawee Oct 1 '15 at 21:35
1
$\begingroup$

You are certainly missing something out. $$U_p |x_0 \rangle = \exp(-i b \hat{x}) |x_0 \rangle =\exp(-i b x_0) |x_0 \rangle $$ Your equations are clearly wrong which you can see from $$\langle x_0|U_p^\dagger p U_p |x_0\rangle =\langle x_0|p |x_0\rangle+b $$ using your second equation. Using your third equation one would get $$\langle x|U_p^\dagger p U_p |x\rangle =\langle x|p |x\rangle $$ which is wrong.

So $$\langle x|U_p^\dagger U_x^\dagger |\psi \rangle =\exp(i b x) \psi(x+a) $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.